© 2018 danted2015

Week 4-Multiplying and Dividing Radicals

Now on week four we started to look at multiplying and dividing radicals.

Let do an example:

(2\sqrt{3} + 3\sqrt{5}) (\sqrt{3} - 2\sqrt{5})

First multiply them together and remember unlike adding and subtracting you don’t need to have the same radicand to do the equation.

2\sqrt{9} - 4\sqrt{15} + 3\sqrt{15} - 6\sqrt{25}

Then add the radicals with the same radicand together.

2\sqrt{9} - \sqrt{15} - 6\sqrt{25}

Finally simplify.

\sqrt{36} - \sqrt{15} - (6)(5) 6 - \sqrt{15} - 30

Final answer: -24 - \sqrt{15}

And there you have it, now you know how to multiply radicals.

Post a Comment

Your email is never published nor shared. Required fields are marked *

*
*

You may use these HTML tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>

Skip to toolbar